Early Postnatal Seizures in a Neonate with Wolf–Hirschhorn Syndrome - Go, Hayato; Haneda, Kentaro; Maeda, Hajime; Ogasawara, Kei; Imamura, Takashi; Momoi, Nobuo; Hosoya, Mitsuaki (American Journal of Perinatology Reports, 2016)
Background Wolf–Hirschhorn syndrome (WHS), which is characterized by a typical facial appearance, growth retardation, mental retardation, seizures, and congenital cardiac defects, has an estimated incidence of 1 per 50,000 births.Case We report a case of a low birth weight neonate with WHS and seizures, as well as persistent pulmonary hypertension in the early neonatal period. Apgar scores were 6 (1 minute) and 8 (5 minutes) with evident retraction. After admission to the neonatal intensive care unit, the patient had tonic–clonic seizures with epilepticus 30 minute after birth. Although the seizures were uncontrollable, continuous thiopental administration was effective for seizure mitigation.Conclusion Neonatal seizures with WHS occur rarely. This is the first case report on seizures just after birth in a neonate with WHS.
Keywords: Wolf–Hirschhorn syndrome; seizure; neonate; persistent pulmonary hypertension